Criminal (2006), volume 1 ebook Coward. - Brubaker, Ed (Criminal (2006), 2015)
The bestselling crime series returns in strikingly designed new editions from Image, starting where it all began: CRIMINAL, VOL. 1: COWARD. a new take on noir that turned the heist story on its head and created a whole new underworld for BRUBAKER & PHILLIPS to explore. BRUBAKER & PHILLIPSÍ recent series FATALE and The FADE OUT have brought their work to a wider audience of new readers, and now is the perfect time to show them the work that made the award-winning teamÍs reputation! Brubaker and PhillipsÍ books have always been about eight years ahead of their time.î -Brian K. Vaughan Author: Ed Brubaker. Illustrator: Sean Phillips, Val Staples . 2015 Basement Gang Inc.